The association between suicidal behaviour and violence, sexual abuse, and parental substance abuse among Sami and Greenlandic adolescents: the WBYG study and the NAAHS - Høilo Granheim Ida Pauline; Kvernmo Siv; Silviken Anne; Lytken Larsen Christina Viskum (Scandinavian Journal of Child and Adolescent Psychiatry and Psychology, 2023)
For young Indigenous people, suicide is one of the leading causes of death, and high rates in Arctic areas indicate serious health and societal concerns. More knowledge is needed, as suicidal behaviour predicts later death by suicide. The aim of this study was to investigate associations between suicidal thoughts and suicide attempts and negative life events, including violence, sexual abuse, and parental substance abuse, in Sami and Greenlandic adolescents, within and between groups and gender.